(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Unfortunately, the term "gastritis" has been incorrectly used to refer to various diseases of the upper abdominal cavity, but true gastritis refers to inflammation of the stomach lining (stomach lining). All or part of the gastric mucosa may be involved.Gastritis or inflammation of the gastric mucosa is one of the most common human diseases. According to statistics, about 80-90% of people have experienced an episode of the disease at least once in their lives. In old age, 70-90% of people suffer from various forms of gastritis. The chronic form of gastritis can develop into peptic ulcers, stomach cancer . Gastritis can be acute and chronic. Acute gastritis can be characterized as erosive (injured areas where cells of the mucous membrane are destroyed or lost) and unpleasant. Chronic gastritis is characterized by histopathology (appearance of the gastric mucosa) with long-lasting symptoms . Although many proposals have been made, there is no generally accepted classification system. This information is focused on true gastritis.